Infant feeding—a scoping review for Nordic Nutrition Recommendations 2023 - Hörnell, Agneta; Lagström, Hanna (Swedish Nutrition Foundation, 2026)
The 2012 edition of the Nordic Nutrition Recommendations (NNR) included recommendations on breastfeeding, based on the most recent guidelines and recommendations from major national food and health authorities and organizations, systematic reviews, and some original research. For NNR 2023, the scope has been expanded and also includes formula feeding and the introduction of solid food. The main focus in this scoping review is on infants aged 0-12 months but also considers parts both before and beyond the first year, as the concept of 'the first 1000 days' emphasizes the importance of factors during pregnancy and the first 2 years of life for immediate and later health: physical as well as emotional and mental health. Breastmilk is the natural and sustainable way to feed an infant during the first months of life. Numerous studies have indicated immediate as well as long-term beneficial effects of breastfeeding on health for both the infant and the breastfeeding mother, and from a public health perspective, it is therefore important to protect, support, and promote breastfeeding. For full-term, normal weight infants, breastmilk is sufficient as the only form of nutrition for the first 6 months, except for vitamin D that needs to be given as supplement. The World Health Organization (WHO) and several other authoritative bodies therefore recommend exclusive breastfeeding during the first 6 months. Starting solids at about 6 months is necessary for both nutritional and developmental reasons. According to the European Food Safety Authority (EFSA) and the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN), solid foods are safe to give from 4 months although exclusive breastfeeding until 6 months is the desirable goal. Breastfeeding can continue together with complementary foods as long as it is mutually desired by the mother and child. If breastfeeding is not enough or for some reason discontinued before the infant is 4 months of age, the infant should be fed infant formula, and, when possible, breastfeeding should be continued alongside the formula feeding. If the infant is 4 months or older, starting with solids together with continued breastfeeding and/or formula feeding is an option. Infant formulas have been developed for infants who are not breastfed or do not get enough breastmilk. Home-made formula should not be given.